Dimensions of Leader Anger Expression Unveiled: How Anger Intensity and Gender of Leader and Observer Affect Perceptions of Leadership Effectiveness and Status Conferral - Yun, Dongwon; Jung, Heajung; Ashihara, Kelly (Frontiers in Psychology, 2020)
While significant organizational research evaluates effective leadership traits and decades of psychological research has investigated emotion, there is a lack of consensus in organizational behavior research related to whether emotion expressed by a leader elicits positive or negative outcomes. We seek to augment existing research by exploring the effect of three dimensions, namely the intensity of anger expressed, the gender of the leader, and the gender of the observer on perceptions of leadership effectiveness and future status conferral. In Study 1, we recruited 40 participants from a well-known U.S. university to select appropriate terms attributable to intense, moderate and neutral levels of anger expression. In Study 2, we recruited a diverse pool of 296 participants and employed a quasi-experimental method by randomly assigning participants into one of the anger expression intensity and leader gender conditions. Participants were asked to read a vignette in which a male or a female leader respond to an anger-provoking situation with different levels of anger expression and answer questions on perceived leadership effectiveness and future status conferral of the leader. Our study findings demonstrated that a leader demonstrating no anger was perceived higher in leadership effectiveness than a leader showing either moderate or intense anger. Juxtaposed to these results, for future status conferral, a leader expressing no anger was perceived as higher in future status than a leader expressing moderate anger without significant difference found between no anger and intense anger. We also found a significant main effect of observer gender with female participants giving lower ratings for leadership effectiveness and status conferral than male participants. Possible explanations and practical implications regarding gender-specific findings are also discussed.